Assessment оf Anthropogenic Load оn the Territory оf the Beshtaugor Reserve - N. V. Denisova (Наука. Инновации. Технологии)
Introduction. The need for functional zoning of specially protected natural areas (SPNA) is due to the need to choose the most effective methods for protecting landscape and biological diversity, the presence of limited economic activity permitted on the territory of the protected landscape, as well as the recreational attractiveness of the territory of the Beshtaugorsky reserve. The need for zoning is explained by the diversity of natural complexes, the types of impact on them by various groups of visitors and the local population, and the corresponding management methods.Materials and research methods. The information base for the study was the materials of field studies of the influence of recreation on landscape components in the Beshtaugorsky reserve of the growing seasons 2021–2022. To identify the types of economic activity, multi-temporal remote sensing data (Landsat) were used. Spatial data processing was carried out using the geographic information system Qgis 3.10.Research results and their discussion. Modern methods of processing spatial data made it possible to identify the main types of land use of the Beshtaugorsky reserve, to map valuable resources and centers of high biodiversity, the growth of specially protected species. In the course of the work, the recreational load on 38 test sites was studied and mapped. The degree of influence of recreation is described, the stages of recreational digression of sites are determined. The result was the creation of a recommended scheme for the functional zoning of the reserve with the allocation of 4 zones within the boundaries of the protected areas and 2 outside the boundaries of the protected areas.Conclusions. Functional zoning of protected areas is a recognized effective method of territory modeling. The division of the Beshtaugorsky reserve into separate areas with recommended types and modes of use should contribute to the planning of management measures, the elimination of conflicts in nature management and the conservation of valuable biological resources through spatial and temporal restrictions.